Effect of fiber type on strength of quasi-isotropic bonded/unbonded plastic composites subjected to tension and compression loadings - Okumuş Fuat (Science and Engineering of Composite Materials, 2013)
In the present study, the effects of different types of fibers on the strength of quasi-isotropic silicon carbide/epoxy composite laminate with reinforced hole were investigated. The composite panels under tension and compression loadings were investigated. The finite element method was used to verify the experimental results. MATLAB R-2012 was used as software to apply the finite element analysis. A rectangular element with nine nodes was chosen. A composite plate was meshed into 64 elements and 288 nodes. It was simply supported with in-plane loading conditions. Two types of reinforcement boundary conditions were investigated: adhesive bonded and snug-fit unbonded plug. For each case, five different sizes of hole diameter were used. In addition, three different types of reinforcing material (steel, aluminum, and E-glass) were employed.